PERUMUSAN KONSEP PENYATUAN KALENDER MADZHAB ULIL AMRI PERSEPEKTIF SYAR’I DAN ASTRONOMI - Muhammad Nurkhanif (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
In determining the concept of the Islamic calendar, it can be traced through the concepts it offers regarding the determination of the beginning of the day, the number of days each month, and the determination of the beginning of the month. The start of the day begins with the setting of the sun, the number of days each month is not fixed or constant but depends on the actual position of the new moon at the end of a month. This research is a literature review based on a descriptive analytical critique approach. The results of this study indicate that there is a need for the MUA Madzhab